Testing of Selection Criteria for Screening of Oil Palm Genotypes Partially Resistant to Ganoderma Boninense in Main-Nursery - Azwar, Rasidin; Siregar, Muhammad Mustiqa; Pakpahan, Loly VA; Purba, Bobby (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2023)
Resistance to basal stem rot (BSR) caused by Ganoderma boninense is now one of the main breeding objectives by many oil palm breeders. Many studies reported that resistance to G. boninense is partial or incomplete resistance.Screening at a longer period in main-nursery is also needed to see genetic variation in rate of infection (‘r) among genotypes. The objective of this study was to test several criteria suitable for identifying genotypes to have low infection rate. Two hundreds of DxP crosses between 16 dura lines and three Pisifera palms were made for testing of their resistance to G. boninense in main-nursery. Since G. boninense is a root disease, its effect on root would be direct and selection based on FRW must be very reliable and accurate. Genotypes which had values better than average value were selected as moderately resistant genotypes to G. boninense. The results showed that: (1) there were differences in fastness of infection and severity of the disease; (2) variation in DS among tested crosses increase with time and reach maximum at the 12th MAI; (3) only four selection criteria had significant correlation FRW, namely, FBW (0.74), AUDPC (-0.261), DS (-0.233), ‘r (-0.205); and (4) four selection criteria which gave the closest results to FRW criterion consecutively were FBW (73%), AUDPC (65%), ‘r (64%), DS (63%). It could be concluded that main-nursery screening could identify genotypes with lower ‘r value. AUDPC and ‘r values are suitable to be used as selection criteria for selecting oil palm genotypes partially resistant to G. boninense in main- nursery screening.